Familial Absent Uvula With Velopharyngeal Incompetence—A New Syndrome?. (April 2020) - Sommerlad, Brian; Seselgyte, Rimante; Lees, Melissa; Pauws, Erwin; Stanier, Philip; Sell, Debbie
We present a family with a previously undescribed abnormality of the palate and oropharynx which involved the absence of the uvula and the anterior pillar of the fauces, rudimentary posterior pillar of the fauces, and hypernasality. Eight family members over 4 generations are affected in a pattern consistent with autosomal dominant inheritance. A causal role for the FOXF2 gene has been identified and previously reported. We describe the management of the proband, which involved attempting to lengthen the palate and to retroposition the abnormally anteriorly directed velar musculature, along with speech therapy.